Expenses for Dwelling – Comparisons by Regions and Territories in Latvia - Sloka, Biruta; Tora, Ginta; Buligina, Ilze; Dzelme, Juris (Journal of Service, Innovation and Sustainable Development, 2021)
Social inclusion and the reduction of inequalities are becoming an increasingly pressing problem in a number of OECD countries with changes in population demographic patterns: population ageing and income inequality. The development of the free market leads to income inequalities and social problems such as unemployment, the "shadow" economy, the loss of membership of a community group, self-development. Initially, by creating solutions to problems, economic inequalities for different groups of society are being investigated, by analysing housing spending, the possibilities to overcome challenging economic and social problems by comparing data by region and territory in Latvia. Housing aspects are influencing social inclusion and quality of life. To those aspects are developed many research in many countries and finding different good practices and innovative solutions which could be useful for many other countries. Aim of the research is to investigate the role of housing for social inclusion and analyse statistical data in Latvia by regions, by administrative territories (cities and rural areas) and by household size. Research methods applied in current research: analysis of scientific findings reflected in scientific publications, analysis of differences in regions in Latvia, analysis of differences by territories in Latvia (cities and rural areas), analysis of differences by household size by testing statistical hypotheses with t – test and analysis of variance – ANOVA.
The research was supported by the NATIONAL RESEARCH PROGRAMME “LATVIAN HERITAGE AND FUTURE CHALLENGES FOR THE SUSTAINABILITY OF THE STATE” project “CHALLENGES FOR THE LATVIAN STATE AND SOCIETY AND THE SOLUTIONS IN INTERNATIONAL CONTEXT" (INTERFRAME-LV, Project No.VPP-IZM-2018/1-0005).
Keywords: regions; inequalities; expenses for dwelling; social and economic stratification; Research Subject Categories::SOCIAL SCIENCES::Business and economics